2013
DOI: 10.1292/jvms.12-0131
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Mutant Prevention Concentrations and Mutation Frequencies against Enrofloxacin for Avian Pathogenic <i>Escherichia coli</i> Isolates

Abstract: ABSTRACT. Clinical efficacies of mutant prevention concentration (MPC) and mutant selection window (MSW) hypotheses have been evaluated for human clinical isolates. We tested the MSW hypothesis by evaluating the relationships between MPCs and mutation frequencies against enrofloxacin for avian pathogenic Escherichia coli (APEC) isolates. Mutation frequencies of strains with MPC:MIC ratios of 8 to 16 were significantly higher than those of strains with an MPC:MIC ratio of 4. Mutation frequencies and MPCs of ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
3
2
1
Order By: Relevance
“…This corresponded with MPC/MIC ratios of 4 (MIC 0.032 μg/mL) or 8 (MIC 0.016 μg/mL). These results dovetail with other reports of MPC measurements in E. coli and APEC strains [ 14 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…This corresponded with MPC/MIC ratios of 4 (MIC 0.032 μg/mL) or 8 (MIC 0.016 μg/mL). These results dovetail with other reports of MPC measurements in E. coli and APEC strains [ 14 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that tva (A) raises the MPC and widens the MSW. Mutants were only recovered from isolates harbouring tva(A) and the geometric mean of mutation frequency was 1.88 × 10 −8 , similar to mutation rates reported for E. coli and S. enterica exposed to quinolones (Randall et al, 2004 ; Ozawa and Asai, 2013 ).…”
Section: Resultssupporting
confidence: 80%
“…We applied the principles of the mutation prevention concentration (MPC) hypothesis, which defines the antibiotic concentration at which mutations giving rise to resistance do not occur (Drlica and Zhao, 2007 ), when exposing isolates to inhibitory tiamulin concentrations. The MPC has been applied to assess the development of resistance to various antibiotics including quinolones, macrolides, tetracyclines, and pleuromutilins in many bacterial species including Escherichia coli, Salmonella enterica, Mycoplasma gallisepticum , and Staphylococcus aureus (Randall et al, 2004 ; Drlica and Zhao, 2007 ; Ozawa and Asai, 2013 ; Zhang et al, 2017 ). Maintaining antibiotic concentrations above the MPC during therapy is thought to help reduce the development of resistance (Drlica and Zhao, 2007 ) and we related our findings to published tiamulin pharmacokinetic and pharmacodynamic parameters in pigs to help inform veterinary options for the treatment of SD.…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Jurado et al 14 , who found no significant differences among different enrofloxacin dosage schemes that were administered orally to broiler chickens. Although various studies have showed that dosage can have an effect on the emergence of resistance, 34,35,60,61 the results of the present study suggest that it does not have an effect on the selection and spread of resistance. Grouping the referred studies with regards to commensal versus pathogenic E. coli isolates, the mutation frequencies of the strains were compared.…”
Section: Treatment Dosecontrasting
confidence: 78%